Boerhaave syndrome: A rare complication of cosmetic surgery - Laurinda Castellani (Revista Brasileira de Cirurgia Plástica)
Introduction: The objective of this case report is to alert surgeons to a possible postoperative complication of long cosmetic surgery under general anesthesia. Boerhaave syndrome is a serious life-threatening disease that requires diagnosis within 12 hours and proper treatment. Case report: A 58-year-old female patient presented with vomiting and nausea after abdominoplasty and mastopexy under general anesthesia. Results: The patient underwent dermolipectomy and mastopexy using the inferior pedicle technique under spinal anesthesia. Four hours after the operation, she presented several episodes of vomiting. Ten hours after the operation, she reported painful swallowing followed by generalized severe pain and presented severe dyspnea, sweating, pallor, and a 90/50 mmHg blood pressure. As the condition worsened, the patient was referred to the intensive care unit where she was intubated and underwent laboratory tests, thoracentesis, and radiological examinations. The patient currently uses an esophageal prosthesis. Conclusions: The literature suggests avoiding prolonged surgery, especially under general anesthesia, because of the risk of carbon dioxide retention, which may lead to postoperative emetic crisis in patients with a history of esophageal disease. It also suggests paying attention to symptoms, not excluding the possibility of Boerhaave syndrome.